Application of the subsequent injury categorisation model for longitudinal injury surveillance in elite rugby and cricket: intersport comparisons and inter-rater reliability of coding. Issue 17 (1st March 2017) - Moore, Isabel S; Mount, Stephen; Mathema, Prabhat; Ranson, Craig
Abstract : Background: When an athlete has more than one injury over a time period, it is important to determine if these are related to each other or not. The subsequent injury categorisation (SIC) model is a method designed to consider the relationship between an index injury and subsequent injury(ies). Objective: The primary aim was to apply SIC to longitudinal injury data from two team sports: rugby union and cricket. The secondary aim was to determine SIC inter-rater reliability. Methods: Rugby union (time-loss; TL) and cricket (TL and non-time-loss; NTL) injuries sustained between 2011 and 2014 within one international team, respectively, were recorded using international consensus methods. SIC was applied by multiple raters, team clinicians, non-team clinicians, and a sports scientist. Weighted kappa and Cohen's kappa scores were calculated for inter-rater reliability of the rugby union TL injuries and cricket NTL and TL injuries. Results: 67% and 51% of the subsequent injuries in rugby union and cricket respectively were categorised as injuries to a different body part not related to an index injury (SIC code 10). At least moderate agreement (weighted and Cohen kappa ≥0.60) was observed for team clinicians and the non-team clinician for both sports. Including NTL and TL injuries increased agreement between team clinician and non-team clinician, but not between clinician and sports scientist. Conclusion: The most common subsequent injury in both sports was an injury to a different body part that was not related to an index injury. The SIC model was generally reliable, with the highest agreement between clinicians working within the same team. Recommendations for future use of SIC are provided based on the proximity of the rater to the team and the raters' level of clinical knowledge.